THE STRUCTURE AND REACTIONS OF ANNOTININE - Betts, Eileen Elizabeth (My University, 1958)
A study of the oxidation reactions of annotinine lactamdiol provided chemical evidence that ring A of annotinine was sixmembered and confirmed that the ether ring in annotinine was an epoxide ring. The detailed structure of ring B of annotinine was elucidated through a study of the reactions of diphenyldesoxodihydroannotinine. Unsuccessful attempts were made to correlate the structure of annotinine with the structures of lycopodine and other Lycopodium alkaloids.
Keywords: Annotinine; Oxidation; Lycopodium; Alkaloids; Lactone Ring; Diphenyldesoxodihydroannotinine